Sözleşmenin değişen şartlara uyarlanması - Anacur, Sebahattin (My University, 2011)
Sözleşmenin değişen şartlara uyarlanması isimli bu çalışma, yüksek lisans bitirme tezidir. Genel anlamda sözleşmenin değişen şartlara uyarlanması kavramı, sözleşme taraflar arasında kurulduktan sonra şartların başlangıçta öngörülemez şekilde değişmesinin sözleşmeye ve edimlerin ifasına olan etkisini ifade etmektedir. Çalışmanın birinci bölümünde sözleşmenin değişen şartlara uyarlanmasına ilişkin iki temel ilke, yani ‘ahde vefa’ ve ‘clausula rebus sic stantibus’ ilkeleri incelenmektedir. Daha sonra karşılaştırmalı hukukta sözleşmenin değişen şartlara uyarlanması konusu incelenmektedir. Türk Hukukunda sözleşmenin değişen şartları uyarlanması ise gerek 818 Sayılı Borçlar Kanunu gerekse 6098 Sayılı Türk Borçlar Kanunu bağlamında değerlendirilmiştir. Çalışmanın ikinci bölümünde konuyla ilgili teoriler, sözleşmenin yorumlanması ve sözleşmenin tamamlanması kavramları ile bunların sözleşmenin değişen şartlara uyarlanması kavramıyla olan ilişkisi irdelenmektedir. Çalışmanın üçüncü ve son bölümünde sözleşmenin değişen şartlara uyarlanmasının çeşitleri ile hâkimin sözleşmeyi değişen şartlara uyarlaması kavramı amaç, kapsam, şart ve sonuçları itibariyle incelenmektedir. Çalışma sonuç bölümüyle sona ermektedir.

This study, titled “Adaptation of Contract to Changing Conditions”, is a postgraduate (master’s degree) graduation thesis. In general, the ‘adaptation of contract to changing conditions’ concept refers to the effects of change of conditions to an extent being unforeseeable at the beginning after establishment of contract by and between the sides thereto on the contract and the contractual obligations. The first part of the study deals with and discusses two basic principles underlying the adaptation of contract to changing conditions, namely “pacta sund servanda” (keeping one’s words) and “clausula rebus sic stantibus” (clause on adapting oneself to the changing conditions). Then, the subject of adaptation of contract to changing conditions is dealt with in the light of comparative law. The adaptation of contract to changing conditions in the Turkish Law is reviewed and discussed in the light of both the Code of Obligations no. 818 and the Turkish Code of Obligations no. 6098. In the second part of the study, the legal theories in this field, and the interpretation of contract and completion of contract concepts and their relations with the concept of adaptation of contract to changing conditions are examined. And the third and last part of the study addresses the types of adaptation of contract to changing conditions and the concept of adaptation of contract to changing conditions in terms of its purpose, scope, conditions and results. The study ends with a conclusions part.
Keywords: Özel Hukuk; Sözleşmeler_Hukuk